What are you Really Drinking? - Iain Russell; Stephen Gibb; Lloyd Fermine; Kendall Park (Australasian Accounting, Business and Finance Journal, 2009)
This poster considers issues in the marketing of “Vitamin Water”. Issues considered include: social responsibility, health issues and marketing ethical issues.